An exploratory analysis on waste management in Italy: A focus on waste disposed in landfill. (30th November 2016) - Agovino, Massimiliano; Ferrara, Maria; Garofalo, Antonio
Highlights: We analyze the driving factors of separate waste collection with a focus on waste disposed in landfill. We apply both cluser analysis and Exploratory Spatial Data Analysis techniques to the Italian provinces. An environment with high institutional quality promotes the recyling and reduces landfill. Abstract: The aim of this paper is to analyze the waste management process with a focus on waste disposed in landfills. The results of our analysis provide guidelines for actions geared at improving the waste management. We apply cluster analysis and Exploratory Spatial Data Analysis (ESDA) techniques to 103 Italian provinces for the year 2011. Thus we are allowed to identify spatial correlation processes and spatial clusters. The results of our investigation show a dual structure in the distribution of landfill disposal rate. Moreover, they importantly suggest that institutional quality and pro-environmental behaviour are significant factors in the waste management process.